2019
DOI: 10.5539/ijef.v11n9p29
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Financial Reporting Quality of Listed Companies in Developing Countries: Evidence from Ghana

Abstract: The adoption of International Financial Reporting Standards (IFRS) in Ghana is expected to improve the quality of financial reporting among companies in Ghana. This paper assesses the extent to which financial reports of companies listed on the Ghana Stock Exchange (GSE) meet financial reporting quality (FRQ) dimensions of IFRS. It was a descriptive study that employed two experienced professional chartered accountants who practice as independent auditors to use FRQ criteria to assess financial reports of 20 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
(62 reference statements)
3
11
0
Order By: Relevance
“…The study findings in table 3 imply that the financial reporting quality of Zambian listed companies can be described as average or moderate and these results are consistent with the findings from Mbawuni (2019) in Ghana. Contrary to Chen et al, (2010); Osasere and Ilaboya (2018); Mensah (2021) who found significant improvement in FRQ following IFRS adoption, the year to year mean results show no significant increase (1.1%) in the financial reporting quality over the period under review (2012 to 2018).…”
Section: Discussion Of Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…The study findings in table 3 imply that the financial reporting quality of Zambian listed companies can be described as average or moderate and these results are consistent with the findings from Mbawuni (2019) in Ghana. Contrary to Chen et al, (2010); Osasere and Ilaboya (2018); Mensah (2021) who found significant improvement in FRQ following IFRS adoption, the year to year mean results show no significant increase (1.1%) in the financial reporting quality over the period under review (2012 to 2018).…”
Section: Discussion Of Resultssupporting
confidence: 83%
“…Listed companies mostly made no disclosures concerning the "comply or explain" application in the annual report(F5) and provided mostly no information concerning bonuses of the board of directors in the annual report(F7). Further, companies provided no glossary in the annual reports(U4) consistent with the findings by Mbawuni, (2019) in Ghana.…”
Section: Discussion Of Resultsmentioning
confidence: 68%
See 3 more Smart Citations